Inconsistencies and Misleading Information in Officially Approved Prescribing Information From Three Major Drug Markets. Issue 5 (25th July 2014) - Pfistermeister, B; Saß, A; Criegee‐Rieck, M; Bürkle, T; Fromm, M F; Maas, R
<x xml:space="preserve">Abstract</x> The summary of product characteristics (SPC) should provide information for the safe prescription and use of a drug. We evaluated the consistency of critical interaction warnings, the quality of presentation of undesirable effects as well as concordance of critical information of representative drugs marketed in the United States, the UK, and Germany. Reciprocal warnings regarding drug–drug interactions that constitute contraindications were frequently missing in the SPCs of the drugs concerned (all countries >40%). Most SPCs did not explicitly exclude adverse reactions considered not reasonably attributable to the use of the drug. Comparing SPCs of different generic brands of the same drug, only 60, 10, and 20% of the US, UK, and German SPCs, respectively, provided identical contraindications. Current SPCs contain inconsistencies and misleading data that are not compatible with the purpose of SPCs, which is to provide a basis for the safe prescription and use of drugs. Clinical Pharmacology & Therapeutics (2014); 96 5, 616–624. doi:10.1038/clpt.2014.156